High-capacity and high-first-effect biomass-based hard carbon composite negative electrode material as well as preparation method and application of high-capacity and high-first-effect biomass-based hard carbon composite negative electrode material

Through the preparation method of biomass-based hard carbon composite anode material, the problem of low capacity and first-time Coulomb efficiency in the prior art is solved, high capacity, high efficiency and excellent cycling performance are achieved, and the overall performance of sodium ion batteries is improved.

CN119774578AActive Publication Date: 2025-04-08GUANGDONG DONGDAO NEW ENERGY +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411873150.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-08
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The first time the hard carbon negative electrode material developed at this stage is the low efficiency and capacity of the Coulombian, which seriously restricts the development of sodium ion batteries.

Method used

By pre-carbonizing and pickling the biomass, and adding AlCl3 and SnCl4 to the asphalt, nanoAl2O3 and nanoSnO2 particles are generated to form modified asphalt, and then impregnating and carbonizing with the hard carbon precursor, a biomass-based hard carbon composite anode material with a core-shell structure is prepared.

Benefits of technology

It achieves high capacity, high first-time Coulomb efficiency and excellent cycling performance, effectively improving the electrode interface stability and cycling stability of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005196224850000111
    Figure BDA0005196224850000111
Patent Text Reader

Abstract

The invention provides a high-capacity and high-first-efficiency biomass-based hard carbon composite negative electrode material and a preparation method and application of the high-capacity and high-first-efficiency biomass-based hard carbon composite negative electrode material. The biomass-based hard carbon composite negative electrode material has high capacity and first coulombic efficiency, and also has excellent cycle performance. AlCl3 and SnCl4 are added into molten asphalt, the AlCl3 and the SnCl4 react with water in the asphalt to generate nano Al2O3 particles and nano SnO2 particles to obtain modified asphalt, and after the modified asphalt is prepared into a solution, pores of a hard carbon precursor can be filled with the solution and a coating layer can be formed on the surface of the hard carbon precursor in the process of dipping the solution with the hard carbon precursor; in the high-temperature carbonization process, a hard carbon precursor is converted into hard carbon, nano SnO2 is reduced into nano Sn particles by carbon, asphalt is converted into amorphous carbon, the nano Sn particles, the amorphous carbon and nano Al2O3 particles are uniformly distributed in pores and on the surface of the hard carbon, and synchronous modification of the interior and the outer surface of the hard carbon is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode materials for sodium ion batteries, and specifically relates to a high-capacity, high-initial-efficiency biomass-based hard carbon composite negative electrode material, and a preparation method and use thereof. Background Art

[0002] With the rapid development of the electric vehicle market, the demand for lithium-ion batteries has also surged. However, the lithium resources in the earth's crust are limited, which makes the cost of lithium-ion batteries high. At the same time, the working principle of sodium-ion batteries is similar to that of lithium-ion batteries. They have an energy density close to that of lithium-ion batteries. In addition, sodium-ion resources are abundant, evenly distributed, and low in cost. They are expected to be used in large-scale energy storage devices.

[0003] Hard carbon is the most commonly used negative electrode material for commercial sodium-ion batteries. At present, there are two main raw materials for the preparation of hard carbon, namely petroleum coal and biomass. Petroleum coal materials are widely available, and the hard carbon prepared has stable performance and high carbon yield, but due to its structural characteristics, its capacity is lower than other materials; biomass as a carbon source has become the preferred raw material for the preparation of hard carbon due to its environmental friendliness and low cost. However, the first coulombic efficiency and capacity of the hard carbon negative electrode materials currently developed are low, which seriously restricts the development of sodium-ion batteries. Therefore, it is urgent to develop a hard carbon negative electrode material with high capacity and first coulombic efficiency. Summary of the invention

[0004] In order to improve the problems of low first coulombic efficiency and capacity of biomass-based hard carbon negative electrode materials in the prior art, the present invention provides a high-capacity, high-first-efficiency biomass-based hard carbon composite negative electrode material and its preparation method and use. The biomass-based hard carbon composite negative electrode material has high capacity and first coulombic efficiency, and also has excellent cycle performance.

[0005] The object of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a biomass-based hard carbon composite negative electrode material, the preparation method comprising the following steps:

[0007] (1) pre-carbonizing the biomass under a nitrogen atmosphere to obtain a pre-carbonized product;

[0008] (2) mixing the pre-carbonized product of step (1) with an acid solution, impregnating, filtering, and washing with water until neutral to obtain a hard carbon precursor;

[0009] (3) placing the asphalt in a reaction kettle and heating it to 120-160° C., adding AlCl 3 and SnCl 4 under stirring conditions, and reacting for 0.5-1 hour to obtain modified asphalt;

[0010] (4) mixing the modified asphalt obtained in step (3) with an organic solvent to obtain a modified asphalt solution;

[0011] (5) placing the hard carbon precursor of step (2) into a reactor, evacuating the reactor, adding the modified asphalt solution of step (4), stirring the mixed solution, and pressurizing and impregnating. After the pressurized impregnation is completed, the pressure is reduced to make the pressure inside and outside the reactor the same, nitrogen is introduced, and the organic solvent is removed by heating to obtain the impregnated hard carbon precursor;

[0012] (6) Placing the impregnated hard carbon precursor of step (5) in a high-temperature furnace and performing carbonization treatment under a nitrogen atmosphere to prepare the biomass-based hard carbon composite negative electrode material.

[0013] According to an embodiment of the present invention, in step (1), the source of the biomass is not particularly defined, and may be, for example, at least one of lychee wood, apple wood, poplar wood, bamboo, fruit shell, straw, coconut shell and corn cob.

[0014] According to an embodiment of the present invention, in step (1), the biomass raw material is preferably washed, then dried at 60-120° C., and then preliminarily crushed after drying.

[0015] According to an embodiment of the present invention, in step (1), the temperature of the pre-carbonization treatment is 300°C-600°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C; the time of the pre-carbonization treatment is 1-6 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours. The pre-carbonization treatment can remove organic matter in the biomass and obtain a pre-carbonized product containing holes.

[0016] According to an embodiment of the present invention, in step (1), after the pre-carbonization treatment is completed, the pre-carbonized product is preferably cooled to room temperature in the furnace.

[0017] According to an embodiment of the present invention, in step (1), the product after the pre-carbonization treatment is preferably pulverized to obtain a pre-carbonized product with a median particle size of 5-8 μm.

[0018] According to an embodiment of the present invention, in step (2), the pH value of the acid solution is 3-4.

[0019] According to an embodiment of the present invention, in step (2), the acid solution may be at least one of a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution, a nitric acid aqueous solution, and a hydrofluoric acid aqueous solution.

[0020] According to an embodiment of the present invention, in step (2), the immersion time is 12-24 hours, for example, 12 hours, 16 hours, 18 hours or 24 hours.

[0021] According to an embodiment of the present invention, in step (2), the impregnation is performed at normal pressure.

[0022] According to an embodiment of the present invention, in step (2), the pre-carbonized product of step (1) and the acid solution are mixed under stirring conditions, and then the pre-carbonized product is completely immersed in the acid solution, that is, the acid solution completely covers the pre-carbonized product.

[0023] According to an embodiment of the present invention, in step (2), after the immersion is completed, the acid solution is removed by filtering, and then the solid phase component is washed with deionized water until it becomes neutral.

[0024] According to an embodiment of the present invention, in step (3), the softening point of the asphalt is 65-75°C, for example, 65°C, 70°C or 75°C.

[0025] According to an embodiment of the present invention, in step (3), the water content in the asphalt is 2-3wt%, for example, 2wt%, 2.2wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.8wt% or 3wt%.

[0026] According to an embodiment of the present invention, in step (3), the asphalt is placed in a reaction kettle and heated to 120°C, 130°C, 140°C, 150°C or 160°C, and reacted at this temperature for 0.5-1 hour. During the reaction, the AlCl3 and SnCl4 react with water in the asphalt to generate nano-Al2O3 and nano-SnO2 particles, and the generated nano-Al2O3 and nano-SnO2 particles are evenly distributed in the asphalt, thereby preparing the modified asphalt. Compared with the method of directly adding nano-Al2O3 and nano-SnO2 particles to asphalt to obtain modified asphalt, the method of in-situ synthesis of nano-Al2O3 and nano-SnO2 particles of the present invention can make nano-Al2O3 and nano-SnO2 particles evenly distributed in asphalt, and in the subsequent carbonization process, nano-SnO2 is reduced to metal Sn and evenly distributed in the amorphous carbon after asphalt carbonization, and amorphous carbon will exist in the pores and surface of hard carbon, which is conducive to improving the capacity of hard carbon composite negative electrode materials; at the same time, the method of in-situ synthesis of nano-sized Al2O3 and nano-SnO2 particles of the present invention can also avoid the situation that the modified asphalt cannot enter the interior of the pre-carbonized product during the impregnation process due to uneven dispersion of metal oxides (such as agglomeration), thereby failing to effectively improve the first coulomb efficiency and capacity of the negative electrode material. At the same time, reacting at this temperature can also increase the softening point of asphalt (the softening point of asphalt is increased from 65-75°C to 75-95°C).

[0027] According to an embodiment of the present invention, in step (3), the softening point of the modified asphalt is 75-95°C, for example, 75°C, 80°C, 85°C, 90°C or 95°C.

[0028] According to an embodiment of the present invention, in step (3), the mass ratio of AlCl3 to asphalt is (0.5-3):100, for example, 0.5:100, 0.6:100, 0.8:100, 1.0:100, 1.2:100, 1.5:100, 1.8:100, 2:100, 2.2:100, 2.5:100, 2.8:100 or 3:100.

[0029] According to an embodiment of the present invention, in step (3), the mass ratio of SnCl4 to asphalt is (2-12):100, for example, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100 or 12:100.

[0030] According to an embodiment of the present invention, in step (4), the organic solvent is selected from hydrocarbon organic solvents, such as any one of wash oil, naphthalene oil, phenol oil, or a mixture of two thereof.

[0031] According to an embodiment of the present invention, in step (4), the mass ratio of the modified asphalt to the organic solvent is 1:(1-1.5), for example, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5.

[0032] According to an embodiment of the present invention, in step (4), the mixing is carried out under stirring conditions, and the modified asphalt can be fully dissolved in the organic solvent by stirring to form a modified asphalt solution.

[0033] According to an embodiment of the present invention, in step (5), the mass ratio of the modified asphalt solution to the hard carbon precursor of step (2) is (40-60):1, for example, 40:1, 45:1, 50:1, 55:1 or 60:1.

[0034] According to an embodiment of the present invention, in step (5), the stirring speed is 500-800 r / min.

[0035] According to an embodiment of the present invention, in step (5), the method of adding the modified asphalt solution of step (4) is, for example: opening the modified asphalt solution suction valve, sucking the modified asphalt solution of step (4) into the reactor, and closing the suction valve after the liquid is added to stop vacuuming.

[0036] According to an embodiment of the present invention, in step (5), the vacuum degree of the reactor is 0.07-0.09 MPa.

[0037] According to an embodiment of the present invention, in step (5), the pressure of the pressurized impregnation is 1 MPa-3 MPa, for example, 1 MPa, 1.5 MPa, 2 MPa, 2.5 MPa, 3 MPa; the time of the pressurized impregnation is 1-5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.

[0038] According to an embodiment of the present invention, in step (5), the heating temperature is 200-300° C.; the heating time is not particularly defined, and the heating time is sufficient until the organic solvent is completely removed.

[0039] According to an embodiment of the present invention, in step (6), the temperature of the carbonization treatment is 900°C-1200°C, for example, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C; the time of the carbonization treatment is 1-6 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours.

[0040] According to an embodiment of the present invention, in step (6), the product after the carbonization treatment is preferably dispersed to obtain a biomass-based hard carbon composite negative electrode material with a median particle size of 5-8 μm.

[0041] The present invention also provides a biomass-based hard carbon composite negative electrode material prepared by the above method.

[0042] According to an embodiment of the present invention, the biomass-based hard carbon composite negative electrode material has a core-shell structure, the core includes hard carbon, nano-Sn particles, amorphous carbon and nano-Al2O3 particles; the nano-Sn particles, amorphous carbon and nano-Al2O3 particles are distributed in the pores of the hard carbon; the shell is a composite of nano-Sn particles, nano-Al2O3 particles and amorphous carbon.

[0043] According to an embodiment of the present invention, the median particle size of the nano Sn particles is 25-35 nm, for example, 30 nm.

[0044] According to an embodiment of the present invention, the median particle size of the nano-Al2O3 particles is 30-45 nm, for example, 35 nm or 40 nm.

[0045] According to an embodiment of the present invention, the median particle size of the biomass-based hard carbon composite negative electrode material is 5-8 μm.

[0046] According to an embodiment of the present invention, the thickness of the shell is 80-120 nm.

[0047] The present invention also provides the use of the above-mentioned biomass-based hard carbon composite negative electrode material, which is used in sodium ion batteries, preferably used to prepare the negative electrode of sodium ion batteries.

[0048] The present invention also provides a negative electrode for a sodium ion battery, wherein the negative electrode comprises the above-mentioned biomass-based hard carbon composite negative electrode material.

[0049] The present invention also provides a sodium ion battery, which comprises the above-mentioned biomass-based hard carbon composite negative electrode material.

[0050] Beneficial effects of the present invention:

[0051] The present invention sequentially performs pre-carbonization treatment and acid washing treatment on biomass, and simultaneously adds AlCl3 and SnCl4 into molten asphalt, wherein AlCl3 and SnCl4 react with water in the asphalt to generate nano Al2O3 particles and nano SnO2 particles, thereby obtaining modified asphalt, wherein the nano Al2O3 and nano SnO2 are uniformly dispersed in the modified asphalt; the modified asphalt is prepared into a solution, and during the process of impregnation with a hard carbon precursor, the modified asphalt can be filled into the pores of the hard carbon precursor and can form a coating layer on the surface of the hard carbon precursor; during the high-temperature carbonization process, the hard carbon precursor is transformed into hard carbon, the nano SnO2 is reduced into nano Sn particles by carbon, the asphalt is transformed into amorphous carbon, the nano Sn particles, the amorphous carbon and the nano Al2O3 particles are uniformly distributed in the pores and on the surface of the hard carbon, thereby realizing the simultaneous modification of the inside and the outside surface of the hard carbon. In addition, nano-Al2O3 particles and amorphous carbon can not only enhance the structural integrity and strength of the hard carbon composite negative electrode material, but also effectively inhibit the decomposition of the electrolyte on the surface of the hard carbon composite negative electrode material, which can effectively improve the stability of the electrode interface and improve the cycle stability and first coulombic efficiency of the sodium ion battery. Nano-Sn particles can increase the capacity of the hard carbon composite negative electrode material, so that the prepared hard carbon composite negative electrode material exhibits high first coulombic efficiency, high capacity and excellent cycle performance. DETAILED DESCRIPTION

[0052] The preparation method of the present invention will be described in further detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0053] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0054] Example 1

[0055] (1) Carbonizing coconut shell at 400° C. for 4 h under a nitrogen atmosphere, cooling to room temperature, and then pulverizing to obtain material 1;

[0056] (2) soaking the material 1 of step (1) in a hydrochloric acid solution with a pH of 3 for 15 hours, filtering, washing with deionized water until neutral, and drying to obtain material 2;

[0057] (3) 100 g of asphalt (softening point 68°C) was placed in a reactor and heated to 120°C. 1 g of AlCl3 and 6 g of SnCl4 were added to the molten asphalt under stirring conditions (500 r / min) and reacted for 0.5 hours to obtain modified asphalt (softening point 78°C);

[0058] (4) mixing 100 g of the modified asphalt obtained in step (3) with 100 g of washing oil and stirring to fully dissolve the asphalt to obtain a modified asphalt solution;

[0059] (5) 4 g of material 2 was placed in a reactor and evacuated for 60 min. When the vacuum degree of the reactor reached 0.07 MPa, the modified asphalt solution suction valve was opened to completely suck 200 g of the modified asphalt solution obtained in step (4) into the reactor. After the liquid was added, the suction valve was closed and the evacuation was stopped. At the same time, the mixed solution was stirred (20 r / min) for 40 min and then immersed at 1.5 MPa for 3 h. After the immersion was completed, the pressure was reduced to make the pressure inside and outside the reactor the same, and nitrogen was introduced. The mixture was heated to 230° C. to remove the wash oil to obtain material 3;

[0060] (6) The material 3 of step (5) is placed in a high-temperature furnace, carbonized at 1200° C. for 4 h in a nitrogen atmosphere, and then pulverized after cooling to room temperature to obtain a biomass-based hard carbon composite negative electrode material.

[0061] The biomass-based hard carbon composite negative electrode material has a core-shell structure, wherein the core comprises hard carbon, nano-Sn particles, amorphous carbon and nano-Al2O3 particles; the nano-Sn particles, amorphous carbon and nano-Al2O3 particles are distributed in the pores of the hard carbon; and the shell is a composite of nano-Sn particles, nano-Al2O3 particles and amorphous carbon.

[0062] Example 2

[0063] (1) The fruit shell was carbonized at 500°C for 2 h under a nitrogen atmosphere, cooled to room temperature, and then pulverized to obtain material 1;

[0064] (2) soaking the material 1 of step (1) in a nitric acid solution with a pH of 4 for 14 hours, filtering, washing with deionized water until neutral, and drying to obtain material 2;

[0065] (3) 100 g of asphalt (softening point 70°C) was placed in a reactor and heated to 120°C. 1.5 g of AlCl3 and 4 g of SnCl4 were added to the molten asphalt under stirring conditions (500 r / min) and reacted for 0.6 hours to obtain modified asphalt (softening point 85°C);

[0066] (4) mixing 100 g of the modified asphalt obtained in step (3) with 120 g of naphthalene oil and stirring to fully dissolve the asphalt to obtain a modified asphalt solution;

[0067] (5) 5 g of material 2 was placed in a reactor and evacuated for 60 min. When the vacuum degree of the reactor reached 0.07 MPa, the modified asphalt solution suction valve was opened to completely suck 240 g of the modified asphalt solution obtained in step (4) into the reactor. After the liquid was sucked in, the suction valve was closed and the evacuation was stopped. At the same time, the mixed solution was stirred (30 r / min) for 30 min and then impregnated under 2 MPa. After the impregnation was completed, the pressure inside and outside the reactor was reduced to the same, and nitrogen was introduced. The reactor was heated to 250° C. to remove the naphthalene oil to obtain material 3;

[0068] (6) The material 3 of step (5) is placed in a high-temperature furnace, carbonized at 1400° C. for 3 h in a nitrogen atmosphere, and then pulverized after cooling to room temperature to obtain a biomass-based hard carbon composite negative electrode material.

[0069] The biomass-based hard carbon composite negative electrode material has a core-shell structure, wherein the core comprises hard carbon, nano-Sn particles, amorphous carbon and nano-Al2O3 particles; the nano-Sn particles, amorphous carbon and nano-Al2O3 particles are distributed in the pores of the hard carbon; and the shell is a composite of nano-Sn particles, nano-Al2O3 particles and amorphous carbon.

[0070] Example 3

[0071] (1) The coconut shell was carbonized at 350° C. for 6 h under a nitrogen atmosphere, cooled to room temperature, and then crushed to obtain material 1;

[0072] (2) soaking the material 1 of step (1) in a hydrochloric acid solution with a pH of 3 for 15 hours, filtering, washing with deionized water until neutral, and drying to obtain material 2;

[0073] (3) 100 g of asphalt (softening point 75°C) was placed in a reactor and heated to 100°C. 2 g of AlCl3 and 7 g of SnCl4 were added to the molten asphalt under stirring conditions (650 r / min) and reacted for 0.5 hours to obtain modified asphalt (softening point 95°C);

[0074] (4) mixing 100 g of the modified asphalt obtained in step (3) with 150 g of phenol oil and stirring to fully dissolve the asphalt to obtain a modified asphalt solution;

[0075] (5) 5 g of material 2 was placed in a reactor and evacuated for 60 min. When the vacuum degree of the reactor reached 0.07 MPa, the modified asphalt solution suction valve was opened to completely suck 250 g of the modified asphalt solution obtained in step (4) into the reactor. After the liquid was added, the suction valve was closed and the evacuation was stopped. At the same time, the mixed solution was stirred (20 r / min) for 40 min and then impregnated under 2.5 MPa. After the impregnation was completed, the pressure inside and outside the reactor was reduced to the same, and nitrogen was introduced. The reactor was heated to 280° C. to remove the phenol oil to obtain material 3;

[0076] (6) The material 3 of step (5) is placed in a high-temperature furnace, carbonized at 1200° C. for 4 h in a nitrogen atmosphere, and then pulverized after cooling to room temperature to obtain a biomass-based hard carbon composite negative electrode material.

[0077] The biomass-based hard carbon composite negative electrode material has a core-shell structure, wherein the core comprises hard carbon, nano-Sn particles, amorphous carbon and nano-Al2O3 particles; the nano-Sn particles, amorphous carbon and nano-Al2O3 particles are distributed in the pores of the hard carbon; and the shell is a composite of nano-Sn particles, nano-Al2O3 particles and amorphous carbon.

[0078] Example 4

[0079] (1) carbonizing coconut shell at 600° C. for 2 h under a nitrogen atmosphere, cooling to room temperature, and then pulverizing to obtain material 1;

[0080] (2) soaking the material 1 of step (1) in a hydrochloric acid aqueous solution with a pH of 4 for 20 hours, filtering, washing with deionized water until neutral, and drying to obtain material 2;

[0081] (3) 100 g of asphalt (softening point 72°C) was placed in a reactor and heated to 120°C. 0.6 g of AlCl3 and 6 g of SnCl4 were added to the molten asphalt under stirring conditions (600 r / min) and reacted for 0.5 hours to obtain modified asphalt (softening point 80°C);

[0082] (4) mixing 100 g of the modified asphalt obtained in step (3) with 100 g of washing oil and stirring to fully dissolve the asphalt to obtain a modified asphalt solution;

[0083] (5) 5 g of material 2 was placed in a reactor and vacuumed for 60 min. When the vacuum degree of the reactor reached 0.07 MPa, the modified asphalt solution suction valve was opened to completely suck 200 g of the modified asphalt solution obtained in step (4) into the reactor. After the liquid was added, the suction valve was closed and the vacuum was stopped. At the same time, the mixed solution was stirred (25 r / min) for 40 min and then impregnated under 1.5 MPa. After the impregnation was completed, the pressure was reduced to make the pressure inside and outside the reactor the same, and nitrogen was introduced and heated to 250° C. to remove the wash oil to obtain material 3;

[0084] (6) The material 3 of step (5) is placed in a high-temperature furnace, carbonized at 1200° C. for 4 h in a nitrogen atmosphere, and then pulverized after cooling to room temperature to obtain a biomass-based hard carbon composite negative electrode material.

[0085] The biomass-based hard carbon composite negative electrode material has a core-shell structure, wherein the core comprises hard carbon, nano-Sn particles, amorphous carbon and nano-Al2O3 particles; the nano-Sn particles, amorphous carbon and nano-Al2O3 particles are distributed in the pores of the hard carbon; and the shell is a composite of nano-Sn particles, nano-Al2O3 particles and amorphous carbon.

[0086] Comparative Example 1

[0087] (1) Carbonizing coconut shell at 400° C. for 4 h under a nitrogen atmosphere, cooling to room temperature, and then pulverizing to obtain material 1;

[0088] (2) soaking the material 1 of step (1) in a hydrochloric acid solution with a pH of 3 for 15 hours, filtering, washing with deionized water until neutral, and drying to obtain material 2;

[0089] (3) 100 g of asphalt (softening point 68°C) was placed in a reactor and heated to 120°C for 0.5 hours to obtain modified asphalt;

[0090] (4) mixing 100 g of the modified asphalt obtained in step (3) with 100 g of washing oil and stirring to fully dissolve the asphalt to obtain a modified asphalt solution;

[0091] (5) 4 g of material 2 was placed in a reactor and evacuated for 60 min. When the vacuum degree of the reactor reached 0.07 MPa, the modified asphalt solution suction valve was opened to completely suck 200 g of the modified asphalt solution obtained in step (4) into the reactor. After the liquid was added, the suction valve was closed and the evacuation was stopped. At the same time, the mixed solution was stirred (20 r / min) for 40 min and then immersed at 1.5 MPa for 3 h. After the immersion was completed, the pressure was reduced to make the pressure inside and outside the reactor the same, and nitrogen was introduced. The mixture was heated to 230° C. to remove the wash oil to obtain material 3;

[0092] (6) The material 3 of step (5) is placed in a high-temperature furnace, carbonized at 1200° C. for 4 h in a nitrogen atmosphere, and then pulverized after cooling to room temperature to obtain a biomass-based hard carbon composite negative electrode material.

[0093] The biomass-based hard carbon composite negative electrode material has a core-shell structure, wherein the core comprises hard carbon and amorphous carbon; the amorphous carbon is distributed in the pores of the hard carbon; and the shell is amorphous carbon.

[0094] The biomass-based hard carbon composite negative electrode materials prepared in the above Examples 1-4 and Comparative Example 1 were used as negative electrode materials for sodium ion batteries, and electrochemical performance tests were performed as follows:

[0095] The biomass-based hard carbon composite negative electrode material, conductive agent Super P, binder sodium carboxymethyl cellulose (CMC) and aqueous binder (SBR) prepared above were weighed in a mass ratio of 95:2:1.5:1.5, and after being fully ground in an agate mortar, a small amount of deionized water was added to mix to form a uniform black paste slurry. The slurries were coated on a copper foil current collector as a test electrode, and a metal sodium sheet was used as a reference electrode to assemble into a button cell. The electrolyte was 1M sodium hexafluorophosphate dissolved in a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1. 5wt.% of fluoroethylene carbonate (FEC) was added to the electrolyte as an additive. Glass fiber was used as a separator, and CR2032 stainless steel was used as a battery shell to assemble into a button cell. The discharge capacity and the first coulomb efficiency were tested at a constant rate of 0.1C in the voltage range of 0.01-3.0V.

[0096] The biomass-based hard carbon composite negative electrode material prepared as above was used as the negative electrode, sodium nickel iron manganese oxide was used as the positive electrode, and 1M-NaPF6+EC:DEC:DMC (volume ratio 1:1:1) solution was used as the electrolyte to assemble a full battery in a stacked manner. The room temperature charge and discharge test was carried out at a rate of 1C with a voltage range of 1.5-3.9V to test the cycle performance.

[0097] Table 1 Electrochemical performance of biomass-based hard carbon composite anode materials

[0098]

[0099] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a biomass-based hard carbon composite negative electrode material, the preparation method comprising the following steps: (1) pre-carbonizing the biomass under a nitrogen atmosphere to prepare a pre-carbonized product; (2) mixing the pre-carbonized product of step (1) with an acid solution, impregnating, filtering, and washing with water until neutral to obtain a hard carbon precursor; (3) placing the asphalt in a reaction kettle and heating it to 120-160° C., adding AlCl 3 and SnCl 4 under stirring conditions, and reacting for 0.5-1 hour to obtain modified asphalt; (4) mixing the modified asphalt obtained in step (3) with an organic solvent to obtain a modified asphalt solution; (5) placing the hard carbon precursor of step (2) into a reactor, evacuating the reactor, adding the modified asphalt solution of step (4), stirring the mixed solution, and pressurizing and impregnating. After the pressurized impregnation is completed, the pressure is reduced to make the pressure inside and outside the reactor the same, nitrogen is introduced, and the organic solvent is removed by heating to obtain the impregnated hard carbon precursor; (6) Placing the impregnated hard carbon precursor of step (5) in a high-temperature furnace and performing carbonization treatment under a nitrogen atmosphere to prepare the biomass-based hard carbon composite negative electrode material.

2. The preparation method according to claim 1, wherein In step (1), the biomass is at least one of lychee wood, apple wood, poplar wood, bamboo, fruit shell, straw, coconut shell and corn cob; And / or, in step (1), the temperature of the pre-carbonization treatment is 300° C.-600° C.; the time of the pre-carbonization treatment is 1-6 hours; And / or, in step (1), the product after the pre-carbonization treatment is crushed to obtain a pre-carbonized product with a median particle size of 5-8 μm; And / or, in step (2), the pH value of the acid solution is 3-4; And / or, in step (2), the acid solution is at least one of a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution, a nitric acid aqueous solution, and a hydrofluoric acid aqueous solution.

3. The preparation method according to claim 1 or 2, wherein In step (3), the softening point of the asphalt is 65-75°C; and / or, in step (3), the water content in the asphalt is 2-3 wt%; And / or, in step (3), the mass ratio of AlCl3 to asphalt is (0.5-3):100; And / or, in step (3), the mass ratio of SnCl4 to asphalt is (2-12):

100.

4. The preparation method according to any one of claims 1 to 3, wherein: In step (4), the organic solvent is selected from any one of wash oil, naphthalene oil, phenol oil or a mixture of two thereof; And / or, in step (4), the mass ratio of the modified asphalt to the organic solvent is 1:(1-1.5).

5. The preparation method according to any one of claims 1 to 4, wherein: In step (5), the mass ratio of the modified asphalt solution to the hard carbon precursor of step (2) is (40-60):1; And / or, in step (5), the pressure of the pressurized impregnation is 1 MPa-3 MPa; the time of the pressurized impregnation is 1-5 hours; And / or, in step (5), the heating temperature is 200-300°C.

6. The preparation method according to any one of claims 1 to 5, wherein: In step (6), the temperature of the carbonization treatment is 900° C.-1200° C.; and the time of the carbonization treatment is 1-6 hours.

7. The biomass-based hard carbon composite negative electrode material prepared by the method according to any one of claims 1 to 6.

8. The biomass-based hard carbon composite negative electrode material according to claim 7, wherein: The biomass-based hard carbon composite negative electrode material has a core-shell structure, wherein the core comprises hard carbon, nano-Sn particles, amorphous carbon and nano-Al2O3 particles; the nano-Sn particles, amorphous carbon and nano-Al2O3 particles are distributed in the pores of the hard carbon; and the shell is a composite of nano-Sn particles, nano-Al2O3 particles and amorphous carbon. Preferably, the median particle size of the nano-Sn particles is 25-35 nm. Preferably, the median particle size of the nano-Al2O3 particles is 30-45 nm. Preferably, the median particle size of the biomass-based hard carbon composite negative electrode material is 5-8 μm. Preferably, the shell has a thickness of 80-120 nm.

9. A negative electrode for a sodium ion battery, the negative electrode comprising the biomass-based hard carbon composite negative electrode material according to claim 7 or 8.

10. A sodium ion battery, comprising the biomass-based hard carbon composite negative electrode material according to claim 7 or 8.

Citation Information

Patent Citations

  • Negative electrode material for sodium-ion battery and preparation method thereof

    CN112038614A

  • Preparation method of nano SnO2 / water-soluble asphalt carbon composite electrode negative electrode material

    CN113562719A

  • Graphene / tin oxide / carbon composite negative electrode material and preparation method and application thereof

    CN116314657A

  • Asphalt-based composite hard carbon material as well as preparation method and application thereof

    CN118495512A

  • Tetratin triphosphide / hard carbon negative electrode composite material as well as preparation method and application thereof

    CN118833786A